Motivation of Physical Education Students in Completing the Final Project - Syafruddin, Muhammad Akbar; Ikadarny, Ikadarny (Universitas Majalengka, 2024)
This research is a descriptive study that aims to determine the motivation of students of the Physical Education, Health and Recreation Study Program of FIK UNM. the sample in this study amounted to 50 people who were determined using purposive sampling technique. The purposive samplin technique is a sample withdrawal technique using certain criteria. The data collection technique was carried out using a Likert scale questionnaire with a choice of 5 (five) answers. The data analysis technique was carried out with descriptive tests to determine the mean value and standard deviation which was then used to determine the data categorization interval. The results showed that 5 students (10%) had very low motivation, 12 students (24%) had low motivation, 11 students (22%) had moderate motivation, and 22 students (44%) had high motivation. The conclusion in this study is that the motivation of students of the Physical Education, Health and Recreation Study Program is in the high category.